2015
DOI: 10.1038/srep09506
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music performance on the transcriptome of professional musicians

Abstract: Music performance by professional musicians involves a wide-spectrum of cognitive and multi-sensory motor skills, whose biological basis is unknown. Several neuroscientific studies have demonstrated that the brains of professional musicians and non-musicians differ structurally and functionally and that musical training enhances cognition. However, the molecules and molecular mechanisms involved in music performance remain largely unexplored. Here, we investigated the effect of music performance on the genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(101 citation statements)
references
References 72 publications
8
92
0
1
Order By: Relevance
“…Interestingly, mammals, including modern humans, have been shown to share similar inner ear structures even with insects23. A shared background of sound perception and production between evolutionarily as distant species as humans and songbirds has been found in our previous studies, where several homologous genes known to affect song learning and singing in songbirds were up-regulated after music perception and performance in humans1112. All these evidence suggest a high evolutionary conservation, or convergent evolution, of molecular mechanisms related to sound perception and production.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Interestingly, mammals, including modern humans, have been shown to share similar inner ear structures even with insects23. A shared background of sound perception and production between evolutionarily as distant species as humans and songbirds has been found in our previous studies, where several homologous genes known to affect song learning and singing in songbirds were up-regulated after music perception and performance in humans1112. All these evidence suggest a high evolutionary conservation, or convergent evolution, of molecular mechanisms related to sound perception and production.…”
mentioning
confidence: 57%
“…). Interestingly, FOS and DUSP1 genes have an increased transcriptional activity in professional musicians after they played musical instruments11. Other candidate genes like FOXP2 and GRIN2B have been shown to be critical for vocal communication in songbirds and speech in humans35363738.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there may be many genes involved in a musical performance, it is interesting that Kanduri et al [50] showed that following a 2-h concert performed by professional musicians, their upregulated genes affected dopaminergic neurotransmission, motor actions, neuronal plasticity, and neurocognitive activities such as learning and memory. Specifically, candidate genes including SNCA, FOS, and DUSP1 were identified, which are known to be involved in song perception and production in songbirds.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster networks of GO-categorized differentially expressed genes were annotated by the database resource Search Tool for the Retrieval of Interacting Genes (STRING) software (v.9.1) (www. string-db.org/) [14]. All associations in STRING are provided with a probabilistic confidence score, representing a functional linkage between two proteins.…”
Section: Functional Annotation and Pathway Analysismentioning
confidence: 99%